Treatment of Developmental Dysplasia of the Hip with Salter Innominate Osteotomy Method, - Kılıç, B., Yücel, A. S., Yaman, Ç., Çatıkkaş, F., Hergüner, G., (My University, 2014)
Background: In this study, we aim to show that salter innominate osteotomy treatment method is effective in maintaining the hip stability and yielding successful results with the support of soft tissue in patients diagnosed with developmental dysplasia of the hip (DDH) and those with unilateral developmental dysplasia of the hip over 18 months. The most important factor in developmental dysplasia of the hip yielding the result is diagnosis and the time of treatment, so it is possible to obtain near-normal results. Salter operation is a current and successful method on condition that pre-operative rules and operation techniques are applied completely and thoroughly in children aged over 1,5. Corrective osteotomies should be added to femoral head in this operation for children aged over four. Methods: A total of 7 patients aged between 19-26 months with unilateral developmental dysplasia of the hip on whom we applied salter innominate osteotomy on different dates were included in our study. In the study, a treatment was performed through salter innominate osteotomy on various dates to 7 patients of the age range of 19-26 months who had total unilateral developmental hip dislocation. Results: Quadriceps were given to the hips of all patients from iliac crest with anterior incision under general anesthesia. Salter innominate osteotomy was applied. Conclusion: In post-op, balanced walking was ensured in 2.5-4.5 months in all patients without any complications except the simple ones (migration of Kirschner wire and soft tissue infection).
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Developmental Dysplasia of The Hip; Salter Pelvic Osteotomy; Salter; Operation; Treatment